Efficient composite flame-retardant electrolyte and preparation method and application thereof
By adding composite flame retardants to the lithium-ion battery electrolyte, perfluoro2-methyl-3-pentanone, ethoxypentafluorocyclic triphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol, the problem of flammable and explosive in high-temperature environments is solved, and the efficient composite flame retardant effect of the battery is achieved, which significantly improves the safety and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411821806.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium-ion battery electrolyte has low thermal stability, flammable and explosiveness, which can easily cause safety hazards such as heat loss, smoke, fire and even explosion in high-temperature environments.
The composite flame retardant perfluoro2-methyl-3-pentanone, ethoxypentafluorocyclic triphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol are added to the electrolyte to form a highly efficient composite flame retardant electrolyte, reducing the flammability of the electrolyte and improving the electrochemical performance of the battery.
It significantly improves the safety performance and electrochemical performance of lithium-ion batteries, reduces the flame retardant risk of batteries at high temperatures, and improves the stability and charge-discharge specific capacity of batteries.
Smart Images

Figure CN119650853A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-efficiency composite flame-retardant electrolyte and a preparation method and application thereof. Background Art
[0002] Since the commercialization of lithium-ion batteries, it has been an indispensable part of portable electronic products. With the further development of the electric vehicle industry and the upgrading of energy storage equipment, high-energy-density power batteries are gradually being promoted. However, safety issues have always been prominent and have not been well resolved. With the widespread controversy caused by the explosion accidents related to lithium-ion batteries used in mobile phones and electric vehicles in recent years, there is an urgent need to improve the safety of lithium-ion batteries, which is the foundation for their long-term and widespread application.
[0003] As an important component of lithium-ion batteries, electrolyte is one of the important causes of battery safety problems. The main component of the lithium-ion battery electrolyte currently used is alkyl carbonate, which has defects such as low thermal stability, flammability and explosion, and a narrow operating temperature range. In a high temperature environment, it is easy to cause thermal runaway of lithium-ion batteries, causing smoke, fire, and even explosion, which endangers personal and property safety. Using flame retardant additives to improve the performance of lithium-ion battery electrolytes is one of the most economical and effective methods. Flame retardant additives have the characteristics of small dosage and significant effect, and can improve or even enhance the functions of conventional electrolytes. At the same time, flame retardant additives can reduce the flammability of organic electrolytes, making them difficult to burn or even non-flammable, while improving their thermal stability. It is a simple and practical safety protection method.
[0004] The existing battery flame retardant solution mainly focuses on adding flame retardants to the electrolyte, while traditional phosphate flame retardants will form decomposition products CHO on the surface of the positive electrode lithium iron phosphate. x O - and LiF x - The positive electrode is corroded by HF, causing irreversible damage, which cannot meet the safety and electrochemical performance requirements of lithium-ion batteries in high temperature environments. In addition, although flame retardants such as perfluoro-2-methyl-3-pentanone flame retardant added to the electrolyte can improve the flame retardant properties to a certain extent, they are expensive and have poor compatibility when used alone, making it difficult to meet the requirements of industrial promotion. Summary of the invention
[0005] The purpose of the present invention is to provide a high-efficiency composite flame-retardant electrolyte and a preparation method and application thereof, so as to overcome the shortcomings of the prior art. The present invention adds composite flame retardants perfluoro-2-methyl-3-pentanone, ethoxypentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol to the electrolyte to obtain a high-efficiency composite flame-retardant electrolyte, which reduces the flammability of the electrolyte and improves the electrochemical performance of the battery.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, the present invention provides a high-efficiency composite flame-retardant electrolyte, comprising an organic solvent, an electrolyte lithium salt and an additive, wherein the additive comprises perfluoro-2-methyl-3-pentanone, ethoxypentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol.
[0008] The inventors found in the research process that although the perfluoro 2-methyl-3-pentanone flame retardant can improve the flame retardant performance to a certain extent, it is expensive and has poor compatibility when used alone. Ethoxy pentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol form a composite flame retardant with perfluoro 2-methyl-3-pentanone. Ethoxy pentafluorophosphazene has two flame retardant elements, P and F, which have a synergistic effect, can reduce the additive dosage of perfluoro 2-methyl-3-pentanone, improve the flame retardant efficiency, and significantly improve the safety performance of the electrolyte; 2-amino-2-hydroxymethyl-1,3-propanediol contains flame retardant elements such as nitrogen (N) and oxygen (O), which improves the flame retardant efficiency. At the same time, its good wettability and buffering properties can effectively combine with ethoxy pentafluorocyclotriphosphazene and perfluoro 2-methyl-3-pentanone.
[0009] In some other embodiments, the concentration of the electrolyte lithium salt in the organic solvent is 0.5-2 mol / L; the volume of the additive in the organic solvent is 1-10%;
[0010] Preferably, the concentration of the electrolyte lithium salt in the organic solvent is 1 mol / L; and the volume of the additive in the organic solvent is 5%.
[0011] In some other embodiments, the mixing volume ratio of the perfluoro-2-methyl-3-pentanone, ethoxypentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol is (1-3): (1-3): 1;
[0012] Preferably, the mixing volume ratio of the perfluoro-2-methyl-3-pentanone, ethoxypentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol is 1:1:1.
[0013] In some other embodiments, the organic solvent includes ethylene carbonate, diethyl carbonate and ethyl methyl carbonate;
[0014] The volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is (1-3):(1-3):1; preferably, the volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is 1:1:1.
[0015] In some other embodiments, the electrolyte lithium salt is one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate and lithium hexafluorophosphate;
[0016] Preferably, the electrolyte lithium salt is lithium hexafluorophosphate.
[0017] In a second aspect, the present invention provides a method for preparing the high-efficiency composite flame-retardant electrolyte described in the first aspect, characterized in that an organic solvent, an electrolyte lithium salt and an additive are mixed to obtain the electrolyte.
[0018] In some other embodiments, the mixing conditions are: room temperature and inert atmosphere.
[0019] In a third aspect, the present invention provides application of the high-efficiency composite flame-retardant electrolyte described in the first aspect in a lithium-ion battery.
[0020] In a fourth aspect, the present invention provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator and the high-efficiency composite flame-retardant electrolyte described in the first aspect.
[0021] In some other embodiments, the lithium-ion battery is a ternary positive electrode material lithium-ion battery, a lithium iron phosphate positive electrode material lithium-ion battery, a lithium iron manganese phosphate positive electrode material lithium-ion battery, a lithium nickel manganese oxide positive electrode material lithium-ion battery, and a high nickel positive electrode material lithium-ion battery.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention adds a newly developed composite flame retardant perfluoro-2-methyl-3-pentanone (PFMP) + ethoxypentafluorocyclotriphosphazene (PFPN) + 2-amino-2-hydroxymethyl-1,3-propanediol (THAM) to the electrolyte to obtain a high-efficiency composite flame retardant electrolyte. The PFPN additive can generate PNO-rich on the positive electrode lithium iron phosphate. – 、NO x – PFMP is also used as an internal fire extinguishing agent and can promote the formation of SEI film on the surface of the negative electrode, thereby reducing the flammability of the electrolyte and improving the performance of the battery. THAM can maintain a stable pH value and help adjust the ionic strength of the solution, thereby affecting the migration rate and separation effect of ions.
[0024] (2) The composite flame retardant of the present invention has two or more flame retardant elements P and F. The synergistic effect of the flame retardant elements can reduce the amount of additives and have a significant flame retardant effect in the self-extinguishing test. At the same time, it improves the electrochemical performance and stability of the battery at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 The combustion pictures of the electrolyte at different times after ignition in the embodiment of the present invention;
[0027] Figure 2 The cycle performance of the battery assembled with the electrolyte in the embodiment of the present invention at 1C rate at 50°C;
[0028] Figure 3 The cycle performance of the battery assembled with the LEDE electrolyte in the embodiment of the present invention at 5C rate at 50°C;
[0029] Figure 4 The cycle performance of the battery assembled with LEDEPPT electrolyte in the embodiment of the present invention at 5C rate at 50°C;
[0030] Figure 5 The charge and discharge curves of the battery assembled with the electrolyte in the embodiment of the present invention at 1C rate at 50°C for (a) the first cycle and (b) the 100th cycle;
[0031] Figure 6 The charge and discharge curves of the battery assembled with the electrolyte in the embodiment of the present invention at 5C rate at 50°C for (a) the 1st, (b) the 500th and (c) the 1000th cycles;
[0032] Figure 7 Electrochemical impedance diagrams of batteries assembled with the electrolytes in the examples of the present invention at (a) 25°C and (b) 50°C. DETAILED DESCRIPTION
[0033] Example 1
[0034] Step 1 Preparation of electrolyte
[0035] First, the carbonate solvent was dehydrated with molecular sieves in a glove box for 12 hours. Ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were dehydrated at room temperature, while ethylene carbonate (EC) was dehydrated at 70°C because of its high melting point and solid state at room temperature. The pre-cooled solvents (EC, DEC, EMC) were mixed in a volume ratio of 1:1:1, and the corresponding mass of lithium salt LiPF6 was added. The electrolyte was configured to be 1MLiPF6+EC / DEC / EMC (1:1:1), and was shaken at room temperature until the lithium salt was completely dissolved. 5% (volume ratio) of the composite flame retardant additive perfluoro-2-methyl-3-pentanone (PFMP), ethoxypentafluorocyclotriphosphazene (PFPN) and 2-amino-2-hydroxymethyl-1,3-propanediol (THAM) were added in a mixing ratio of 1:1:1, and the mixture was shaken to obtain the LEDEPPT electrolyte, which was sealed for use. LEDE electrolyte was free of additives, and other conditions were the same as those of the experimental group. All operations were performed in a glove box filled with argon.
[0036] The same method was used to prepare LEDEPP, LEDEPT, and LEDETP electrolytes according to the following mixing volume ratios: PFMP+PFPN (1:1), PFMP+THAN (1:1), and THAN+PFPN (1:1), respectively.
[0037] Step 2 Preparation of electrode sheets
[0038] Positive electrode sheet: First, weigh 9g of PVDF powder, add 91g of N-methylpyrrolidone (NMP), stir on a magnetic stirrer until the powder is completely dissolved, and prepare a 9% PVDF binder. Weigh the LiFePO4 active material, Super-P, and PVDF binder in a mass ratio of 8:1:1, add them to the small box of the mixer and stir to obtain a uniformly mixed slurry. Apply the slurry on aluminum foil with a 150um coater, and then place the electrode sheet in an 80°C forced air drying oven for 12 hours. After the electrode sheet is completely dry, slice it into circular electrode sheets with a diameter of 14mm, then press the electrode sheet with a pressure of 1MPa, and finally place the electrode sheet in a vacuum drying oven at 110°C and dry it for 24 hours. After weighing, put it in a glove box for use. The surface density of the positive electrode sheet is 3-4mg / cm 2 .
[0039] Negative electrode sheet: Weigh the graphite negative electrode material, Super-P, and PVDF binder in a mass ratio of 8:1:1, add them into the small box of the paddle machine and stir to obtain a uniformly mixed slurry. Apply the slurry on the copper sheet with a 100μm applicator, and then put the electrode sheet into an 80°C forced air drying oven for 12 hours. After the electrode sheet is completely dry, slice it into circular electrode sheets with a diameter of 14mm, and then press the electrode sheet with a pressure of 0.8MPa. Finally, place the electrode sheet in a vacuum drying oven at 110°C and dry it for 24 hours. After weighing, put it in the glove box for use. The surface density of the negative electrode sheet is 3-4mg / cm 2 .
[0040] Step 3: Making button batteries
[0041] The positive electrode sheet coated with LiFePO4 positive electrode material is placed on the negative electrode shell, and after placing the PP separator, 100 μL of electrolyte is added, and then the negative electrode sheet coated with graphite negative electrode material, gasket, and spring are placed in sequence, and finally the positive electrode shell (CR2025) is covered. After assembly, the battery is sealed and packaged using a button battery sealing machine. All the above processes are completed in the glove box. After the battery is left to stand for 12 hours, constant current charge and discharge and other electrochemical tests are performed.
[0042] Step 4: Performance Testing
[0043] (1) Self-extinguishing time test
[0044] The flame retardant performance of the electrolyte is obtained by testing the self-extinguishing time of the electrolyte after ignition. Place 200μL of electrolyte in the battery shell, ignite the flame for 3s, observe and record the extinguishing time of the electrolyte, repeat three times, and the results are as follows Figure 1 As shown. Figure 1 It can be seen that the self-extinguishing time of LEDE electrolyte is 25s, and the self-extinguishing time of LEDEP electrolyte with 5% PFMP added alone is 21s, which is slightly improved; while the self-extinguishing time of LEDEPP, LEDEPT, and LEDETP electrolytes composed of 5% PFMP+PFPN (1:1), PFMP+THAN (1:1), and THAN+PFPN (1:1) are 18s, 20s, and 15s respectively, although they can improve the flame retardant properties of the electrolyte to varying degrees. After adding 5% PFMP+PFPN+THAN (1:1:1) to the LEDE electrolyte, the self-extinguishing time of the composite flame retardant LEDEPPT was 10s after testing, showing the best flame retardant properties.
[0045] During the research and development process, the inventors found that by reducing any one of the above-mentioned additives or replacing the components of the electrolyte, the flame retardant effect of the electrolyte on the battery as a whole was significantly reduced; adding other raw material components on the basis of the additives of this application did not significantly improve the overall effect of the electrolyte, and even reduced the overall effect of the electrolyte. Therefore, the raw material components in the electrolyte of this application play a role in enhancing flame retardancy as a whole, and thus improve the overall safety of lithium batteries. The amount of each raw material in the additive of this application is also very critical. During the experiment, the inventors adjusted the amount of some raw materials in the additives. It was found that the flame retardant effect of the composition after the adjustment of the amount on the electrolyte was significantly reduced.
[0046] (2) Cyclic performance test
[0047] The conditions for the cycle performance test are: 50°C, 1C current cycle charge and discharge, and a voltage range of 2.5–4.2V.
[0048] The two LiFePO4 / graphite batteries assembled with LEDE electrolyte and LEDEPPT electrolyte were left to stand at room temperature for 12 h, and then cycled at 1C at room temperature. Figure 2 shown.
[0049] from Figure 2 It can be seen that in the ordinary battery assembled with LEDE electrolyte, the battery specific capacity is maintained at 70 mAh g after the cycle starts. -1 The charge and discharge capacity of the battery assembled with LEDEPPT electrolyte is basically stable at 120mAh g -1 Compared with batteries without additives, the charge and discharge specific capacity at 50°C is greatly improved, the coulombic efficiency is stable at around 98%, and the capacity retention rate is 92.4%, showing very stable high-temperature electrochemical performance.
[0050] (3) Long cycle performance test
[0051] The conditions for the long cycle performance test are: 50°C, 5C rate, and voltage range of 2.5–4.2V.
[0052] First, the two assembled LiFePO4 / graphite batteries were left to stand at room temperature for 12 hours, and then cycled at 5C current for 1000 times at room temperature. Figure 3 , Figure 4 The cycling performance curves of batteries assembled with LEDE and LEDEPPT electrolytes respectively.
[0053] from Figure 3It can be seen that in the battery assembled with the traditional LEDE electrolyte without flame retardant additives, the battery specific capacity continues to decrease after the cycle starts, and the capacity after 470 cycles is reduced to 20 mAh g -1 , and the change in coulombic efficiency during subsequent cycles shows that the battery's charge and discharge at 50°C is unstable and the battery performance is poor. Figure 4 In the experiment, although the cycle performance of the battery assembled with LEDEPPT electrolyte also decayed within 400 cycles, the specific capacity was basically stable to 90 mAh g after 400 cycles. -1 The capacity retention rate is still greater than 75% until the cycle reaches 1000 times, and the coulombic efficiency is greater than 95%. Compared with the battery assembled with LEDE electrolyte, the performance of the battery using LEDEPPT electrolyte is greatly improved at high temperature.
[0054] (4) Constant current charge and discharge test
[0055] The constant current charge and discharge test conditions are: 50°C, 1C, and the charge and discharge range is 2.5~4.2V.
[0056] The charge and discharge range of the LiFePO4 electrode tested in this experiment is 2.5 to 4.2V. Figure 5 The battery charge and discharge curves before and after adding the flame retardant additive at 1C; Figure 5 (a) Figure 5 (b) The charge and discharge curves of the 1st and 100th cycles, respectively.
[0057] from Figure 5 As can be seen in (a), during the first cycle, there is a certain gap in the charge and discharge specific capacity of the two groups of batteries. As the number of charge and discharge times increases, the gap becomes more obvious. This is because PFPN generates PNO-rich on the positive electrode lithium iron phosphate. - 、NO x - The protective layer reduces the erosion of HF on the positive electrode, effectively protects the positive electrode, and enables the battery to have a higher charge and discharge specific capacity at high temperature.
[0058] Figure 6 The battery charge and discharge performance diagrams before and after adding flame retardant additives at 5C; Figure 6 (a) Figure 6 (b) Figure 6 (c) The charge and discharge curves of the 1st, 500th and 1000th cycles respectively.
[0059] from Figure 6 As can be seen in (a), during the first cycle, the lithium ions embedded in graphite can be released relatively smoothly, and the battery assembled with LEDEPPT electrolyte has a higher specific capacity; Figure 6(b) and Figure 6 (c) It can be seen that during the 500th and 1000th charge and discharge processes, the battery assembled using LEDEPPT electrolyte is more stable in charge and discharge compared to the battery assembled using LEDE electrolyte. This is because the additive promotes the formation of a stable SEI film on the graphite electrode during the cycle. Only when there is a stable SEI film on the electrode surface can lithium ions have a stable channel for embedding and detaching from graphite at high temperatures.
[0060] (5) Electrochemical impedance spectroscopy
[0061] The conditions for electrochemical impedance spectroscopy are: temperature 25°C or 50°C, frequency 0.01 to 10 5 Hz, and the voltage is between 2.5–4.2V.
[0062] Information about the electrochemical processes of the two battery groups is obtained by measuring the impedance response of the system to an AC power supply. 5 The EIS test results of LFP / graphite battery at 25℃ and 50℃ are as follows: Figure 7 shown. Figure 7 (a) and Figure 7 (b) Battery impedance diagrams before and after adding additives at 25℃ and 50℃ respectively.
[0063] Figure 7 (a) It can be seen that the impedance of the LFP / graphite battery assembled with LEDE electrolyte is about 2.8Ω, while the impedance of the battery assembled with LEDEPPT electrolyte is 6.9Ω, which indicates that the addition of PFMP+PFPN+THAM can reduce the impedance of the battery. This may be because the flame retardant promotes the formation of a better interface film on the graphite negative electrode, resulting in a decrease in impedance.
[0064] And in Figure 7 In (b), it can be seen that the impedance of the battery assembled with LEDE electrolyte is 6.6Ω, which is not much different from the battery impedance at 25°C; while the impedance of the battery with 5% PFMP+PFPN+THAM is only 2.5Ω, and the impedance is reduced by 10.7%, showing better electrochemical performance. Lower impedance means that during the lithium ion deintercalation process, the resistance inside the battery is smaller. Therefore, more lithium ions can be deintercalated smoothly, which directly leads to an increase in the charge and discharge capacity of the battery, which is consistent with the previous experimental results.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-efficiency composite flame-retardant electrolyte, comprising an organic solvent, an electrolyte lithium salt and an additive, characterized in that: The additives include perfluoro-2-methyl-3-pentanone, ethoxypentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol.
2. The high-efficiency composite flame-retardant electrolyte according to claim 1, characterized in that: The concentration of the electrolyte lithium salt in the organic solvent is 0.5-2 mol / L; the volume of the additive in the organic solvent is 1-10%; Preferably, the concentration of the electrolyte lithium salt in the organic solvent is 1 mol / L; and the volume of the additive in the organic solvent is 5%.
3. The high-efficiency composite flame-retardant electrolyte according to claim 1, characterized in that: The mixing volume ratio of the perfluoro-2-methyl-3-pentanone, ethoxypentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol is (1-3): (1-3): 1; Preferably, the mixing volume ratio of the perfluoro-2-methyl-3-pentanone, ethoxypentafluorocyclotriphosphazene and 2-amino-2-hydroxymethyl-1,3-propanediol is 1:1:
1.
4. The high-efficiency composite flame-retardant electrolyte according to claim 1, characterized in that: The organic solvent includes ethylene carbonate, diethyl carbonate and ethyl methyl carbonate; The volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is (1-3):(1-3):1; preferably, the volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is 1:1:
1.
5. The high-efficiency composite flame-retardant electrolyte according to claim 1, characterized in that: The electrolyte lithium salt is one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate and lithium hexafluorophosphate; Preferably, the electrolyte lithium salt is lithium hexafluorophosphate.
6. A method for preparing a high-efficiency composite flame-retardant electrolyte according to any one of claims 1 to 5, characterized in that: The organic solvent, electrolyte lithium salt and additives are mixed to obtain the product.
7. The method for preparing a high-efficiency composite flame-retardant electrolyte according to claim 6, characterized in that: The mixing conditions are: room temperature and inert atmosphere.
8. Use of the high-efficiency composite flame-retardant electrolyte according to any one of claims 1 to 5 in a lithium-ion battery.
9. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the high-efficiency composite flame-retardant electrolyte according to any one of claims 1 to 5.
10. The lithium ion battery according to claim 9, characterized in that: Lithium-ion batteries include ternary positive electrode material lithium-ion batteries, lithium iron phosphate positive electrode material lithium-ion batteries, lithium iron manganese phosphate positive electrode material lithium-ion batteries, lithium nickel manganese oxide positive electrode material lithium-ion batteries and high nickel positive electrode material lithium-ion batteries.